FORMULASI MARMALADE JERUK SIAM DENGAN SUBSTITUSI SARI KURMA SUKARI SEBAGAI ALTERNATIF SELAI TINGGI SERAT - Rooiqoh, Qothrunnadaa Fajr (NUTRITURE JOURNAL, 2025)
Crude fiber is the remainder of plant cell walls that are not hydrolyzed by human digestive enzymes. One fruit that contains fiber is Siamese oranges. Citrus fruit can be used in various types of preparations so that its shelf life is longer. Preserving citrus fruit can be done by processing oranges into orange marmalade. Marmalade is a semi-solid food that has a gel-like texture. Substitution using date juice can be done to increase the nutritional content of orange jam which has decreased due to the heating process during production. Therefore, this study aims to determine the fiber content in the Siam orange jam formulation as a substitute for sukari date juice. This research is an experimental study with a Completely Randomized Design (CRD) using the crude fiber test using the Weende method. The formulation of orange marmalade is carried out in 3 formulas with a ratio of orange flesh: orange peel and dates, namely F1 (100%:0); F2 (80%: 20%); F3 (85%: 15%). The research results showed that the most preferred formulation was F3 and the formulation with the highest crude fiber content was F3 with a content of 3%, followed by F2 with a content of 2.5% and F1 with a content of 2%.